Terapi Motorik Kasar Siswa Menggunakan Media Tari Autis pada Sekolah Luar Biasa Autis Laboratorium Universitas Negeri Malang - Mokhamad Prasetyo (Mahesa Research Center, 2021)
This article examines the reasons and analysis of the jaranan dance movements carried out by teachers of the Special School (SLB) of the State University of Malang (UM) Laboratory in order to deal with gross motor weaknesses of autistic students. Jaranan dance that develops in the Java region, generally functions as a community performance at certain events. It was different from the UM Laboratory Autism Special School. In that school, Jaranan dance is used as material in gross motor therapy for autistic students. The research method used is descriptive qualitative. The data comes from interviews with the motion and song coordinator Ninik (40 years), therapists and teachers (45 years old Dewi) and Luthfil curriculum and student coordinator (36 years). The researcher added that the expert resource is a lecturer at the UM Sports Science Faculty, namely Febrita (40 years). In addition to interviews, observation and documentation are used to obtain accurate data. The process of data analysis, namely the data obtained, then reduces the data presentation of the data and finally draws conclusions. The validity of the data was obtained by calculating. Analysis using descriptive. The results of the study: 1) The reason jaranan dance can be used as gross motor therapy for Autism Special School, State University Laboratory of Malang. 2) Results of Rough Motoric Therapy Using the Jaranan Dance of Autistic Students at the Autism Special School, State University of Malang Laboratory.